Preschool and primary school children as multimedia learners - Mikelić Preradović, Nives (Array, 2014)
The use of multimedia in preschool and primary school education presents challenges to teachers and institutions. Today’s children prefer the content presented by graphics, sound and video more than written materials and are impatient for the traditional slow systematic transfer of the learning content. This paper discusses differences and similarities between preschools and primary schools in different countries that introduced multimedia literacy education in their educational program. The empirical research results that are presented in this paper describe current situation and possibilities to adopt the multimedia literacy in the current school system in Croatia.